2020
DOI: 10.14740/jocmr4233
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Hydroxychloroquine in COVID-19: A Systematic Review and Meta-Analysis

Abstract: Background: During the initial phases of the coronavirus disease 2019 (COVID-19) epidemic, there was an unfounded fervor surrounding the use of hydroxychloroquine (HCQ); however, recently, the Centers for Disease Control and Prevention (CDC) has recommended against routine use of HCQ outside of study protocols citing possible adverse outcomes. Methods: Multiple databases were searched to identify articles on COVID-19. An unadjusted odds ratio (OR) was used to calculate the safety and efficacy of HCQ on a rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 16 publications
0
12
0
1
Order By: Relevance
“…Remdesivir, a nucleotide analog active against SARS-CoV-2, has shown modest benefit in severe COVID-19 cases by improving time to recovery ( Beigel et al., 2020 ; Wang et al., 2020b ). Hydroxychloroquine was initially tested in patients based on in vitro studies ( Chen et al., 2020c ; Wang et al., 2020b ), but subsequent meta-analyses and randomized controlled trials have demonstrated no benefit in preventing or treating COVID-19 ( Boulware et al., 2020 ; Tang et al., 2020 ; Ullah et al., 2020 ). Morbidity and mortality due to COVID-19 is largely a consequence of adult respiratory distress syndrome (ARDS) caused by a combination of both hyperinflammatory and hypercoagulable states ( Domingo et al., 2020 ), and thus suppression of these will be key to improving outcomes, as evidenced by use of corticosteroids and current trials employing tocilizumab, an anti-IL-6 receptor antibody used to treat cytokine release syndrome ( Guaraldi et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Remdesivir, a nucleotide analog active against SARS-CoV-2, has shown modest benefit in severe COVID-19 cases by improving time to recovery ( Beigel et al., 2020 ; Wang et al., 2020b ). Hydroxychloroquine was initially tested in patients based on in vitro studies ( Chen et al., 2020c ; Wang et al., 2020b ), but subsequent meta-analyses and randomized controlled trials have demonstrated no benefit in preventing or treating COVID-19 ( Boulware et al., 2020 ; Tang et al., 2020 ; Ullah et al., 2020 ). Morbidity and mortality due to COVID-19 is largely a consequence of adult respiratory distress syndrome (ARDS) caused by a combination of both hyperinflammatory and hypercoagulable states ( Domingo et al., 2020 ), and thus suppression of these will be key to improving outcomes, as evidenced by use of corticosteroids and current trials employing tocilizumab, an anti-IL-6 receptor antibody used to treat cytokine release syndrome ( Guaraldi et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hydroxychloroquine was initially tested in patients based on in vitro studies (Wang et al ., 2020; Z. Chen et al ., 2020), but subsequent meta-analyses and randomized controlled trials have demonstrated no benefit in preventing or treating COVID-19 (Boulware et al ., 2020; Tang et al ., 2020; Ullah et al ., 2020). Morbidity and mortality due to COVID-19 is largely a consequence of adult respiratory distress syndrome (ARDS) caused by a combination of both hyperinflammatory and hypercoagulable states (Domingo et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, the results of these studies were conflicting as regards the ability of hydroxychloroquine to limit the radiologic progression [17][18][19]. Variability may be related to the difference in disease severity and time of re-assessment of chest imaging in different study designs.…”
Section: Sample Size Calculationmentioning
confidence: 99%